Ethics of Disenfranchisement and Voting Rights in the U.S.:Convicted Felons, the Homeless, and Immigrants - Ruth, Terrance (American journal of criminal justice, 2017)
This paper examines the contemporary ethical issues surrounding voting rights of three disenfranchised groups in the U.S.: convicted felons, the homeless, and immigrants. Even in modern countries like the U.S., voting and other forms of political participation are skewed toward the elite, those with higher incomes, those who are employed, and those with more education. Low voter turnout presents serious challenges to democratic responsiveness, or the ability of leaders to respond to the needs and demands of citizens. Hence, voting should be encouraged in accord with the common interest. An important conclusion is that allowing all citizens – irrespective of their status – to vote would give them a voice in the context of governance. This notion is also associated with distributive justice, a philosophical concept that concentrates on just outcomes and consequences.